Analisa Produk Pola Cetakan Lilin yang Diproduksi Menggunakan DIY-CNC-Endmill - Firman Ridwan; Ryan Rahman (Metal: Jurnal Sistem Mekanik dan Termal)
The use of technology in ring jewelry manufacturers in Indonesia is still very limited. Ring jewelers still use traditional methods in the process of forming mold patterns. This causes difficulties in producing ring jewelry that requires precision and high accuracy on each product. Unprecised wax pattern of ring jewelry can result in dimensional errors when product is manufactured so the  dimension is far from the size of the design. To avoid this, it can be overcome by using CNC machine technology. CNC machines can work consistently and precisely. For this reason, therefor, an End-Milling type CNC machines that has accuracy of up to 1/1000 mm is designed. The experiments showed that the results with high accuracy having standard deviation of repeatability of inner diameter 0.020736441, repeatability of outer diameter 0.020493902 and repeatability of thickness 0.043817805.